A Study of optimal solutions to resolve water quality problem from a small creature (larvae) - YOON, Jaehyuk (KDI School, 2023)
This paper aims to find solutions to resolve water quality problem caused by small creatures(larvae). In the past, water quality accidents have been followed up with issues such as leakage of pollutants, improvement of water treatment method, and resolution of aging pipelines. A sand filtration method was introduced to remove turbidity, and chlorine disinfection was started to remove the virus. Activated carbon and ozone methods were introduced to prevent disinfection by-products, and membrane filtration was introduced to remove trace substances. However, the larvae incidents that have occurred nationwide since July 2020 in Incheon are different from existing accidents in that they meet the current tap water treatment standards such as turbidity and CT values. In order to carry out this capstone project, the current standards for preventing and responding to the occurrence of tap water larvae and domestic and foreign research papers were examined through the literature review. The recent Guidelines for the treatment of larvae released by The Ministry of Environment were also reviewed. In addition, the two larvae accidents, which had become a major issue, were intensively analyzed to figure out what problems they had and what methods should be promoted as short-term and mid- to long-term solutions. In this task, each five politic and technical solutions were suggested through data analysis and expert interviews. Among them, the tasks to be solved first were selected through AHP analysis. As a priority, in the policy field, the establishment of long-term financial plans for improving the water quality sector and the improvement of disproportionate budget allocation were selected as priorities. Technically, a plan to optimize the operation of the facility was confirmed as a priority. Currently, the number of events and improvement status are insufficient to carry out quantified pilot research projects, and further research is expected to quantify the related content and lead to more reliable visualized results.
Thesis(Master) -- KDI School: Master of Public Management, 2023
Keywords: Water-supply--Korea (South); Water quality--Korea (South)